PROSES PENGAMBILAN KEPUTUSAN KONSUMEN DAN ATRIBUT PRODUK KOPI INSTAN DALAM SACHET [Consumer Decision Making Process and Product Attributes of Instant Coffee] - Wisnu Satyajaya; Azhari Rangga; Fibra Nurainy; Harun Al Rasyid (Jurnal Teknologi & Industri Hasil Pertanian, 2014)
The objectives of this research were to observe the decision making process and the influence of product attributes in consuming of instant coffee products in sachets. This research used questionnaires to obtain information on the characteristics and consumer behavior of respondents. Data were analyzed using descriptive analysis and importance attributes.  The results showed that process of buying through the stages in the purchase decision process, namely               a). need recognition: the main benefits expected was freshness of coffee, highest frequency was  once a day; and the main barrier was product quality; b). searching of information: the main source was promotion; c). alternative evaluation: The main factor in evaluation was taste, the known brand of instant coffee were Torabika, Nescafe, Kopi Luwak, ABC, Top, Good Day; d). The decision to buy: the main reasons to buy was taste; purchase decision depending on the situation, most influential are friends. e). post-purchase evaluation: customers are willing to keep buying previous products.. The highest product attributes importance of instant coffee were the highest sense of 4.34; aroma 4.23; and freshness of 4.11 which is the characteristics specialty[H1] of coffee. Keywords: consumer, instant coffee, product attributes. [H1] Has been changed